Answer:
![\boxed{\text{6 and 7}}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x0hf3z0pkf66963tnfr8afocalek9pqb2k.png)
Explanation:
1. Set up the equation
Let x = the first integer. Then
x + 1 = the next integer
x(x + 1) = the product of the integers
x(x + 1) = 42
x² + x = 42 Distributed the x
x² + x - 42 = 0
2. Solve for x
(x + 7)(x - 6) = 0 Factored the quadratic
x + 7 = 0 x - 6 = 0 Applied zero product rule
x = -7 x = 6 Solved the binomials
We reject x = -7, because x must be positive
x = 6
x + 1 = 7
![\text{The two consecutive positive integers are \boxed{\textbf{6 and 7}}}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7ob4upoyjnwoygvdodoo5lecpxb7k7nfqy.png)
Check:
6(6+ 1) = 42
6(7) = 42
42 = 42
OK.